Doors wide open? the attitudes of 82nd infantry (Bantay Laya) batallion straight male army personnel toward gay male army colleagues and civil-military operations stakeholders. - Bautista, Maria Theresa Louise
The Philippine Army is a male dominated bastion with a macho warrior culture. Its traditional functions of security and defense have long emphasized masculinity as an important foundation of the institution. Straight men have most of the power and influence in the organization. In 2009, the Armed Forces of the Philippines lifted the gay ban, allowing gay men to serve in the military. The admission of gay men has become a sensitive issue and was viewed as a threat for the emasculation of the institution. There is an apprehension that allowing gay men to work in the army will negatively affect group cohesion and performance, thus, impairing its function as a force. There is also the probability that gay men who have become members of the army will be vulnerable to discrimination. Through focus group discussions, this paper compared the attitude of straight male army officers and enlisted personnel in the 82nd Infantry Battalion toward the gay men they have encountered during civil military operation and toward their gay colleagues in the army. It also looked into the actual behaviour of the straight male army members and the degree of stigmatization experienced by the gay men inside the camp. Their work environment (civil-military operations, combat and office work), living conditions, and leisure were evaluated. The straight male army officers? concept of masculinity was also assessed. The policy responses of the institution after the lift of gay ban were looked into. A key-informant interview with a self-identified gay male army officer was also conducted. This research showed that the Philippine army does not completely accept gay men as part of the institution. In the workplace, gay male members of the army are underestimated and indirectly discriminated in a way that they are not usually sent to combat operations but are mostly assigned to civil-military operations work. This is because of the prevailing stereotype that they are soft and feminine. In the camp?s living conditions, it was found out that some of the straight army members are uncomfortable with the presence of gay men. Superior ranking officers also expressed their sentiment saying that gay male army members may tarnish the reputation of the institution which takes pride in their masculinity. There is also no policy inside the camp that safeguards the welfares of gay men and protects them from discrimination. This goes to show that the Philippine Military is not ready for the lift of gay ban and is yet to set a non-discriminatory environment for the admission of gay men in the institution.